Analysis of the Volmer-Krishtalik mechanism for the chlorine electrode reaction - Fernandez, Jose Luis (2000)
The dependencies of the current density and surface coverage of the adsorbed intermediates on overpotential were established without kinetic approximations for the chlorine electrode reaction under the Volmer-Krishtalic mechanism. Tafelian regions were obtained which slope values cannot be derived from the use of the rate determining step criteria, such as 2.3026(2RT/3F) and 2.3026(RT/F), as well as two or three Tafel regions with different slopes in the same anodic or cathodic curve. The existence of limiting kinetic current densities was also demonstrated. Finally, the results obtained were analysed and discussed, comparing them with those obtained by the usual methods. (C) 2000 Elsevier Science S.A.